Tyrosine Kinase Inhibitor Therapy Discontinuation for Patients with Chronic Myeloid Leukaemia in Clinical Practice - Clark, Richard E. (Curr Hematol Malig Rep, 2019)
PURPOSE: In chronic myeloid leukaemia, tyrosine kinase inhibitor treatment is traditionally given continuously for life. However, these drugs produce excellent responses for many patients, and this is accompanied by survival that is close to normal. This has prompted studies of whether it is possible to stop treatment, thus achieving a treatment-free remission (TFR). RECENT FINDINGS: Most TFR studies have focussed on abrupt cessation in patients with long-standing deep remissions, but recent data suggest that more gradual treatment de-escalation may improve TFR success, and that it may be possible to extend TFR attempts to patients who are in stable major molecular response but not necessarily MR4. SUMMARY: Further data are badly needed on TFR for patients whose remission is less than stable MR4 and on the importance of prior interferon-alpha treatment. Funding TFR trials in a disease with such an excellent outlook is an increasing challenge.